2020
DOI: 10.1200/jco.20.01757
|View full text |Cite
|
Sign up to set email alerts
|

Hepatitis B Virus Screening and Management for Patients With Cancer Prior to Therapy: ASCO Provisional Clinical Opinion Update

Abstract: PURPOSE This Provisional Clinical Opinion update presents a clinically pragmatic approach to hepatitis B virus (HBV) screening and management. PROVISIONAL CLINICAL OPINION All patients anticipating systemic anticancer therapy should be tested for HBV by 3 tests—hepatitis B surface antigen (HBsAg), hepatitis B core antibody (anti-HBc) total immunoglobulin (Ig) or IgG, and antibody to hepatitis B surface antigen—but anticancer therapy should not be delayed. Findings of chronic HBV (HBsAg-positive) or past HBV (H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
127
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 128 publications
(148 citation statements)
references
References 68 publications
(98 reference statements)
3
127
0
1
Order By: Relevance
“…The decision between surveillance or prophylaxis should be tailored according to the healthcare setting and individual patient with careful consideration of the following factors: patient adherence to the surveillance protocol, accessibility to HBV DNA testing, and the total cost of antiviral prophylaxis. Our findings add to the ongoing discussion on the most optimal approach to manage HBV reactivation among patients with cancer 10. ACK N OWLED G M ENTSWe would like to thank Mr Mohamad Haniffa Hasan Mohamed, Ms Alisa Noor Hidayah Sairi, Miss Jaclyn Jia Jun Mah, and Miss Yan Xiang Gan for their assistance in managing the study and collecting data.…”
mentioning
confidence: 76%
See 2 more Smart Citations
“…The decision between surveillance or prophylaxis should be tailored according to the healthcare setting and individual patient with careful consideration of the following factors: patient adherence to the surveillance protocol, accessibility to HBV DNA testing, and the total cost of antiviral prophylaxis. Our findings add to the ongoing discussion on the most optimal approach to manage HBV reactivation among patients with cancer 10. ACK N OWLED G M ENTSWe would like to thank Mr Mohamad Haniffa Hasan Mohamed, Ms Alisa Noor Hidayah Sairi, Miss Jaclyn Jia Jun Mah, and Miss Yan Xiang Gan for their assistance in managing the study and collecting data.…”
mentioning
confidence: 76%
“…An alternative approach would be to monitor HBV DNA levels closely and initiate antiviral treatment only when reactivation is detected to prevent hepatitis. 9,10 Surveillance alone, conducted at frequent and regular intervals, has been shown to exhibit comparable clinical outcomes to antiviral prophylaxis, such as low rates of hepatitis and reactivation-associated death. [11][12][13] Although more visits to the hospital may be required for additional HBV DNA testing, this strategy offers the advantages of lower drug costs and pill burden for cancer patients during and after antineoplastic treatment.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Accordingly, we still have to keep awareness of HBV reactivation during ICI treatment for HBV-HCC. 42 In checkmate-040 and Keynote-224 trials, patients were required to receive effective anti-viral therapy and had a viral load <100 IU/mL before initiating ICI treatment. 5 6 In the real life, however, ICIs would be delivered to more complex populations of patients than those of clinical trials that raise a question to the necessity of keeping low viral load before ICI therapy.…”
Section: Discussionmentioning
confidence: 99%
“…A recent publication suggested that serological HBV should be obtained at baseline and evaluated every 6 months during antiviral therapy. Additionally, it should also be checked at least monthly for the first 3 months after the cessation of antiviral therapy and every 3 months thereafter ( 56 ). Although there is no consensus on duration of antiviral treatment, the majority of recommendations for prophylactic antiviral treatment duration vary from 6 months to 12 months after discontinuation of immunosuppressive therapy ( 10 , 11 , 13 , 54 ).…”
Section: Hbsag-positive Recipientsmentioning
confidence: 99%